Pap smear coverage and effect of knowledge and attitude regarding cervical cancer on utilization of the test by women in Udayapur district of Nepal - Ranabhat, S; Dhungana, G; Neupane, M; Shrestha, R; Tiwari, M (Journal of Chitwan Medical College, 2015)
Background: Cervical cancer prevention, the most common cancer in women in Nepal, is almost nonexistent because of very low pap smear coverage. Material and methods: This study was done to find out pap smear coverage, to assess women’s knowledge about cervical cancer and cervical pap smear, to assess women’s attitude towards cervical pap smear, and to find out association of demographic variables, attitude of women towards pap smear test, and knowledge of cervical cancer and cervical pap smear test with its practice. It was a cross sectional analytical observational study which was carried out in a one-day free health camp organized in Udayapur district of Nepal jointly by Chitwan Medical College and Satya Sai Organization on January 5 of 2013. Participants were interviewed with the help of structured questionnaire. Fisher’s exact test was done to detect association of the variables with pap smear practice. Results: Fisher’s exact test showed that knowledge about pap smear test and attitude towards the test were the only variables which significantly influenced pap smear utilization (p= 0.04). Pap smear utilization was not associated with age-at-marriage, age-at-menarche, parity and age-at-first-childbirth. Conclusion: Pap smear coverage was found to be 7.8% (at 95% CI was 0.02-0.13) which is lower than the average for developing countries. This study has shown that knowledge about pap smear test and attitude towards the test significantly influence pap smear utilization. Therefore, work should be done towards that end to increase pap smear coverage. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11969